Effects of Sowing Dates on Yield and Collar Rot of Chickpea (Cicer Arietinum L.) - Tamang, Sanju; Saha, Poly; Rizal, Shishir (Bangladesh Journal of Botany, 2022)
An experiment was formulated to determine the influence of soil moisture (SM) and soil temperature (ST) on the temporal and spatial distribution of collar rot in chickpea initiated by Sclerotium rolfsii (Sacc.), the most pervasive soil-borne pathogen, recognised as one of the major production constraints worldwide. Variety ‘Anuradha’ was sown at five different dates at an interval of 7 days for the two consecutive years. Progression of disease with varying degree of changes in SM, ST along with the age of the plant were recorded. Result revealed that sowing on 26th November produced maximum seed yield. The rate of disease progression indicated, seedling at the age of 30-35 days is most vulnerable to the pathogen and the disease developed more quickly at an early stage. Despite of the fact that, disease development is dependent on ST and SM conditions, age of the plant is also strong determinant of disease initiation. Bangladesh J. Bot. 51(4): 721-727, 2022 (December)